A)6(x-4)-2=
b)2(x+1)-3(x-1)=
c)-3(y-2)+4(y+2)=
d)5(x-y-1)-4(x+2)=
e)2(3a+b)-2(a-b)=
f)jedna druga(4x-4)-2x+
g)x(x-1)-3(x do drugiej-x)=
h)5a(a-3)-3a(a-5)=
i)3x(x+ jedna trzecia y)-2y(jednadruga x- jednadruga)=

3x-6
a)___ -5
3

3a-9b 2a-4b
b)____ - ______
3 2

2x+6 6x-9
c) _____ - _____
2 3
x-7 x-1
d)4*____ + 9* _____
2 3

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-30T21:34:02+02:00
A)6(x-4)-2=6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)jedna druga(4x-4)-2x=2x-2-2x=-2
g)x(x-1)-3(x do drugiej-x)=x^2-x-3x^2-3x=-2x^2-4x
h)5a(a-3)-3a(a-5)=5a^2-15a-3a^2+15=2a^2-15a+15